Evaluating the use of GPS heights in water conservation applications. Issue 348 (3rd May 2016) - Elaksher, A. F.; Fernald, A.; Kapoko, F.
Abstract : Accurate water level elevations are imperative for water resource management. This paper presents the outcomes of a research study using GPS in measuring water level heights. The authors observed the water elevations of several wells, United States Geological Survey (USGS) gauges and acequia points at three different locations in North–Central New Mexico, USA. Different rapid static and static observation sessions were collected independently and adjusted using the nearby reference control stations. The authors used two different sets of receivers: four Topcon Hiper Lite+ and two Leica GPS1200 The authors were able to examine several network configurations with different continuously operating reference station (CORS) stations. Our findings were analogous to empirically expected errors and showed insignificant differences among the heights obtained from rapid static and static sessions at a 95% confidence level. The authors also compared the results with National Geodetic Survey online positioning users service (NGS OPUS) solutions and confirmed the accuracy of our measurements. As independent measurement technique, we measured the height differences among several of these points with conventional levelling surveys. Our GPS measurements provided small disagreements with height differences obtained with the terrestrial surveys, after the GPS heights were reduced to their orthometric correspondences. Based on these findings, current rapid static GPS positioning methodologies are capable of providing equivalent accuracies as those obtained by static GPS and ground surveying techniques.